A Phenomenological Study of the North Carolina Principal Fellows Program Internship Experience (Journal of School Administration Research and Development, 2026)
This transcendental phenomenology study explored the paid internship experiences of graduates from the North Carolina Principal Fellows Program (NCPFP). The study addressed the question: How does the paid internship experience in Master of School Administration (MSA) programs help graduates prepare for successful leadership in K–12 schools? Nine graduates from the NCPFP answered questions through phenomenological interviewing. The participants reflected on how their internships prepared them for effective leadership in today’s complex educational landscape. Using transcendental phenomenological data analysis, three key themes emerged: professional networking, crisis management, and the authenticity of practice as critical elements in leadership preparation. The results aligned with National Educational Leadership Preparation (NELP) Standard 8 (2018), which underscores the importance of authentic internship experiences in principal development. Implications highlight the need for continued innovation in principal preparation, including diverse instructional strategies, updated curriculum design, and embedded supports for leadership growth and well-being within MSA programs.